Value Education in The Perspective of Western and Islamic Knowledge - Dinar Dewi Kania; Wendi Zarman; Teten Romly (Fakultas Tarbiyah, Universitas Darussalam Gontor, 2017)
The moral-spiritual crisis in the western country has been the cause for the development of the value education concept. The Western concept of value is adopted from study of knowledge, in particular philosophy and social sciences, which is developed in the world of education with all its relative variants. The purpose of this paper is to know the concept of value and value education in the perspective of Western and Islamic knowledge. This paper was prepared as a comparative study between Islam and Western perspective on value with particular focus on philosophy, sociology and pedagogy by using library research. The paper concludes that value in Western conception is relative, created by human ratio and neglects the revelation, whilst Islam puts the revelation as a primary source of values which makes education in Islam means the value of education itself. Therefore, it should not be accepted by Muslims without adequate criticism, because there are some fundamental differences between the Western worldview and the Islamic worldview.